2015
DOI: 10.1186/s12967-015-0756-x
|View full text |Cite
|
Sign up to set email alerts
|

Low 25(OH) D serum levels are related with hip fracture in postmenopausal women: a matched case–control study

Abstract: PurposeThere is limited information on the prevalence of vitamin D deficiency among patients diagnosed with hip fracture in the Chinese Han population. Therefore, the aim of this study was to assess the effects of change in the serum levels of 25-hydroxyvitamin D [25(OH) D] and intact parathyroid hormone (iPTH) among postmenopausal women in North China with confirmed hip fracture.MethodsThis study was done from May 1, 2012 to April 30, 2014. Three hundred and forty-nine postmenopausal women who were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Many people fail to meet the recommended daily intake of calcium (800–1000 mg per day) due to inadequate diet, impaired absorption, or food intolerances [ 57 , 58 ]. Vitamin D 3 , whose active form 1,25(OH) 2 D 3 is a cofactor required for calcium absorption in the gastrointestinal tract, is also strongly correlated with bone density [ 59 ]. Vitamin D insufficiency (25(OH)D 3 serum levels <50 nmol/L) is also not uncommon due to diet, lack of sun exposure, or genetic mutations [ 60 ], and many studies have shown that the majority of postmenopausal women in areas around the world have insufficient vitamin D levels [ 61 , 62 , 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…Many people fail to meet the recommended daily intake of calcium (800–1000 mg per day) due to inadequate diet, impaired absorption, or food intolerances [ 57 , 58 ]. Vitamin D 3 , whose active form 1,25(OH) 2 D 3 is a cofactor required for calcium absorption in the gastrointestinal tract, is also strongly correlated with bone density [ 59 ]. Vitamin D insufficiency (25(OH)D 3 serum levels <50 nmol/L) is also not uncommon due to diet, lack of sun exposure, or genetic mutations [ 60 ], and many studies have shown that the majority of postmenopausal women in areas around the world have insufficient vitamin D levels [ 61 , 62 , 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…The incidences of osteoporosis and fractures is rising rapidly due to the aging society in China [1]. Age is an independent risk factor for fracture and global aging brings urgency to fracture prevention [2]. Abnormal gut microbiota can affect the health of the elderly [3].…”
Section: Introductionmentioning
confidence: 99%
“…We suspected that serum levels of TAMO were associated with osteoporosis. Furthermore, osteoporosis is the main cause of hip fractures [2]. Therefore, the study evaluates the serum levels of Trimethylamine N-Oxide (TMAO), a gut microbial metabolite, in 286 postmenopausal women with hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…15 Among the included patients, we identified the subgroup who sustained a concomitant fracture of the upper limb. 16 In this subgroup, a single fall resulted in both a hip and an upper limb fracture. In addition, total hip BMD of the proximal femur was measured using dual x-ray absorptiometry (Hologic QDR2000/QDR4500; Hologic, Inc. Bedford MA, USA) in all the participants.…”
Section: Clinical Informationmentioning
confidence: 89%
“…Cognitive impairment was assessed with the Mini‐Mental State Examination (MMSE), and a score < 24 indicates the presence of a cognitive impairment . Among the included patients, we identified the subgroup who sustained a concomitant fracture of the upper limb . In this subgroup, a single fall resulted in both a hip and an upper limb fracture.…”
Section: Methodsmentioning
confidence: 99%